Clinical and Dermoscopic Factors for the Identification of Aggressive Histologic Subtypes of Basal Cell Carcinoma - Pampena, Riccardo; Parisi, Gabriele; Benati, Mattia; Borsari, Stefania; Lai, Michela; Paolino, Giovanni; Cesinaro, Anna Maria; Ciardo, Silvana; Farnetani, Francesca; Bassoli, Sara; Argenziano, Giuseppe; Pellacani, Giovanni; et al. (Frontiers in Oncology, 2021)
Background: Infiltrative basal cell carcinoma (BCC) has a higher risk for post-surgical recurrence as compared to the most common low-aggressive superficial and nodular BCC. Independent diagnostic criteria for infiltrative BCC diagnosis have not been still defined. Improving the pre-surgical recognition of infiltrative BCC might significantly reduce the risk of incomplete excision and recurrence. Objective: The aim of this study is to define clinical and dermoscopic criteria that can differentiate infiltrative BCC from the most common low-aggressive superficial and nodular BCC. Methods: Clinical and dermoscopic images of infiltrative, superficial, and nodular BCC were retrospectively retrieved from our database and jointly evaluated by two experienced dermoscopists, blinded for the histologic subtype. Pairwise comparisons between the three histologic subtype were performed and multivariable logistic regression models were constructed in order to define clinical and dermoscopic factors independently associated with each subtype. To validate our findings, two experienced dermoscopists not previously involved in the study were asked to evaluate clinical and dermoscopic images from an external dataset, guessing the proper BCC subtype between infiltrative, nodular and superficial, before and after being provided with the study results. Result: A total of 481 histopathologically proven BCCs (51.4% nodular, 33.9% superficial, and 14.8% infiltrative) were included. We found that infiltrative BCC mostly appeared on the head and neck as an amelanotic hypopigmented plaque or papule, displaying ulceration on dermoscopic examination, along with arborizing and fine superficial telangiectasia. Shiny white structures were also frequently observed. Multivariate regression analysis allowed us to define a clinical-dermoscopic profile of infiltrative BCC. Conclusions: we defined the clinical-dermoscopic profile of infiltrative BCC, allowing to differentiate this variant from superficial and nodular BCC. This will improve pre-surgical recognition of infiltrative forms, reducing the risk for post-surgical recurrence.